Private and public investment in Malaysia: Substitutability or complementarity? - Hassan, Sallahuddin; Abd Karim, Mohd Zaini (2007)
It is generally accepted that the government plays a major role in promoting and/or financing private capital formation. Policymakers and analysts believe that public investment provides a significant stimulus to private investment, and thus serves as an instrument in achieving a high economic growth rate. However, empirically, there is a lack of consensus on whether public investment plays a role as complement or substitute to private investment. Hence, the objective of this study is to ascertain this evidence in the case of Malaysia. Using the error correction model analysis, in the short-run, the results show that public investment does not affect private investment. However, public investment has a positive effect on private investment in the long-run indicating a complementary relationship between the two. This result indicates that, public and private investment complement each other. This might be the case where increase in public capital raises the marginal productivity of private capital, resulting in a greater use of private capital. The results support the Malaysian government policy of using government expenditureswhere most of the government expenditure is on infrastructure investmentas a tool to increase aggregate demand since private investment respond positively to public investment in the long-run.